Understanding the unexplained: The magnitude and correlates of individual differences in residual variance. Issue 12 (3rd May 2021) - Mitchell, David J.; Beckmann, Christa; Biro, Peter A.
Abstract: Behavioral and physiological ecologists have long been interested in explaining the causes and consequences of trait variation, with a focus on individual differences in mean values. However, the majority of phenotypic variation typically occurs within individuals, rather than among individuals (as indicated by average repeatability being less than 0.5). Recent studies have further shown that individuals can also differ in the magnitude of variation that is unexplained by individual variation or environmental factors (i.e., residual variation). The significance of residual variation, or why individuals differ, is largely unexplained, but is important from evolutionary, methodological, and statistical perspectives. Here, we broadly reviewed literature on individual variation in behavior and physiology, and located 39 datasets with sufficient repeated measures to evaluate individual differences in residual variance. We then analyzed these datasets using methods that permit direct comparisons of parameters across studies. This revealed substantial and widespread individual differences in residual variance. The magnitude of individual variation appeared larger in behavioral traits than in physiological traits, and heterogeneity was greater in more controlled situations. We discuss potential ecological and evolutionary implications of individual differences in residual variance and suggest productive future research directions. Abstract : Animals are typically quite unpredictable in behavior with the majority of variance unexplained. We returned to raw data of previously published work, and found almost ubiquitously that individuals vary in their predictability. We discuss potential ecological and evolutionary implications of individual differences in residual variance and suggest productive future research directions.